Juridical Review of Granting Remissions for Prisoners in Correctional Institutions Linked to Permenkumham Number 7 of 2022 - Safitri, Dini; Ikram, Abdurrahman; Sadiman, Akmal Althaffikar; Rahmat, Rahmat (Syiar Hukum, 2024)
This juridical review examines the legal implications of granting remissions for prisoners in correctional institutions under Permenkumham Number 7 of 2022. The regulation, issued by the Ministry of Law and Human Rights of Indonesia, governs the process of remission, a reduction of a prisoner's sentence as a form of leniency or reward for good behavior. The analysis delves into the constitutional and statutory framework surrounding the granting of remissions, evaluating its consistency with principles of justice, equity, and rehabilitation. Furthermore, it explores the procedural aspects of the remission process, including eligibility criteria, application procedures, and discretionary powers of the authorities involved. Additionally, this review examines potential challenges or controversies arising from the implementation of Permenkumham Number 7 of 2022, particularly regarding transparency, accountability, and the potential for abuse or discrimination in granting remissions. By critically examining the legal foundations and practical implications of this regulation, this review aims to contribute to the discourse on criminal justice reform and the protection of prisoners' rights within the Indonesian legal system.